Data-driven gut feeling? a conceptual paper of situational awareness for effective educational leadership in a VUCA environment - Mohamad Halil, Farah Liyana; Abdul Aziz, Nor Azni; Hassan, Aminuddin (Human Resources Management Academic Research Society (HRMARS), 2024)
Effective leaders in education have key characteristics and skills that enable them to navigate the current environment, which is known as volatile, uncertain, complex, and ambiguous, or aptly, VUCA. A number of literatures discussed effective leadership skills such as adaptability, resilience, collaboration, innovation, and strategic thinking. However, one critical skill that is equally important to becoming an effective leader in education has need to be explored in depth, namely Situational Awareness. It refers to the ability of leaders to understand and interpret the context, dynamics, and challenges they face in their own settings. While this concept is recognized as one of the critical skills in fields such as aviation, the military, and healthcare, little attention has been paid to the application of SA in the field of educational leadership. Therefore, this paper will explore the concept of SA and how it can help educational leaders to become effective leaders and decision- makers in dynamic and unpredictable situations, i.e., in the VUCA environment. By exploring the relationship between situational awareness and effective educational leadership, this study aims to provide insights into how educational leaders can develop and improve their situational awareness to better cope with the challenges and opportunities in the VUCA world.